Storytelling Strategy to Improve Indonesian Listening Comprehension - Arozatulo Bawamenewi; Juwita Putri Laia; Tri Rahmat Laoli; Desniat Hardianti Gulo (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2024)
This study evaluates the impact of the storytelling method on learning outcomes in Indonesian language subjects for junior high school students. Through a combination of observations and field notes, significant improvements were observed in students' story comprehension, speaking skills, and creativity. The storytelling method was effective as it engaged students in an interesting and relevant context, boosting their motivation to learn. Expressive storytelling helped students understand and remember storylines better and improved their speaking skills by providing practice opportunities in a supportive atmosphere. Additionally, storytelling fostered creativity by encouraging imagination and improvisation. The study concludes that storytelling enhances students' motivation, interest, speaking skills, listening comprehension, and overall communication abilities. Therefore, it is an effective approach for Indonesian language learning at the junior high school level.